2020
DOI: 10.1371/journal.pone.0235500
|View full text |Cite|
|
Sign up to set email alerts
|

High adherence and low dropout rate in a virtual clinical study of atopic dermatitis through weekly reward-based personalized genetic lifestyle reports

Abstract: Introduction Clinical trials often suffer from significant recruitment barriers, poor adherence, and dropouts, which increase costs and negatively affect trial outcomes. The aim of this study was to examine whether making it virtual and reward-based would enable nationwide recruitment, identify patients with variable disease severity, achieve high adherence, and reduce dropouts. Methods In a siteless, virtual feasibility study, individuals with atopic dermatitis (AD) were recruited online. During the 8-week st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The completion rate for this study was 35% (14/40), which was mostly as a result of unforeseen circumstances during the COVID-19 pandemic; yet, these could be addressed with better participant screening, monitoring, and engagement or by adopting a hybrid approach. Other digital studies have reported a completion rate between 50% and 80% [ 52 , 53 ]. It was cumbersome for participants to use 2 separate apps (ProofPilot and Cara Care), which led to inconsistent tracking with regard to diet and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The completion rate for this study was 35% (14/40), which was mostly as a result of unforeseen circumstances during the COVID-19 pandemic; yet, these could be addressed with better participant screening, monitoring, and engagement or by adopting a hybrid approach. Other digital studies have reported a completion rate between 50% and 80% [ 52 , 53 ]. It was cumbersome for participants to use 2 separate apps (ProofPilot and Cara Care), which led to inconsistent tracking with regard to diet and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is a first‐time analysis of AD data from a previously published 8‐week, noninterventional, observational, fully remote decentralized feasibility study including patients with AD, designed to investigate whether a siteless trial could recruit nationwide, achieve high adherence, and prevent dropouts. 10 Patients with AD were recruited online through advertisements on social media (recruitment data are published elsewhere 10 ), and were included if they were 18 years or older, fulfilled the UK Diagnostic Criteria for Atopic Dermatitis, 11 and had at least one visible AD lesion at the time of recruitment. The AD lesion was confirmed by board certified dermatologists on a photograph taken by the patient as the study was decentralized without visit to a clinical study site.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies show an increase in patient retention rates in DCTs and better compliance with procedures than in conventional trials (due to the home setting, use of electronic reminders, an overall less burdensome participation etc. ), there is no full consensus regarding these aspects in the literature ( 17 , 18 ).…”
Section: The Risks and Benefits Of Dctsmentioning
confidence: 99%